Pengendalian Debit Air Pada Sistem Kran Wudhu Otomatis Menggunakan Mikrokontroler - Hari Anggoro; Sujono Sujono (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The use of conventional water taps for ablution is still very common, although there are many deficiencies in it. One of the drawbacks is that the valve opening on conventional faucets cannot be adjusted automatically so that the water that comes out of the faucet becomes inefficient. In this final project, a water discharge control device is designed in an automatic ablution faucet system using a microcontroller to make water use more efficient during ablution. Control of water discharge in the automatic ablution faucet system uses the HC-SR04 ultrasonic sensor which functions to read the distance of human hands / feet from the ultrasonic sensor. The way the water flow control works in this automatic ablution faucet system is that the valve opening can be adjusted automatically based on the reading of the ultrasonic sensor on the human hand / foot, then the distance detected by the ultrasonic sensor will be sent to the microcontroller which then gives commands to the servo faucet motor. Based on tests that have been carried out 15 times the process of ablution, this automatic ablution faucet system uses 24.05 liters / second of water while the conventional ablution faucet system uses 34.8 liters / second of water. So that the water efficiency obtained in the automatic ablution faucet system against the conventional ablution faucet system is 30.4%.